2020
DOI: 10.1029/2020ja027793
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate Observations of Quasiperiodic Emissions by the Van Allen Probes Spacecraft and Ground‐Based Station Kannuslehto

Abstract: Whistler mode waves observed in the Earth's inner magnetosphere at frequencies between about 0.5 and 4 kHz which exhibit a nearly periodic time modulation of the wave intensity are called quasiperiodic (QP) emissions. Conjugate measurements of QP events at several different locations can be used to estimate their spatial extent and spatiotemporal variability. Results obtained using conjugate QP measurements provided by the ground-based station Kannuslehto (L ≈ 5.5) and the Van Allen Probes spacecraft (L shells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 49 publications
3
10
0
Order By: Relevance
“…Wave vector directions close to vertical are needed on the bottom of the ionosphere in order to allow the wave propagation to the ground. This is consistent with conjugate observations of the emissions by spacecraft and ground-based instruments, which indeed reveal the emissions to extend to lower L-shells on board the spacecraft than on the ground (Bezděková et al, 2020).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Wave vector directions close to vertical are needed on the bottom of the ionosphere in order to allow the wave propagation to the ground. This is consistent with conjugate observations of the emissions by spacecraft and ground-based instruments, which indeed reveal the emissions to extend to lower L-shells on board the spacecraft than on the ground (Bezděková et al, 2020).…”
Section: Resultssupporting
confidence: 90%
“…The observed oblique wave normal angles demonstrate that the wave propagation is primarily unducted (Martinez‐Calderon et al., 2016; Němec et al., 2018). The unducted propagation is believed to be responsible for the same QP modulation being observed over comparatively large regions of space (Bezděková et al., 2020; Němec, Bezděková, et al., 2016; Němec, Hospodarsky, et al., 2016; Němec, Santolík, Parrot, et al., 2013). This is supported by multipoint measurements and detailed time delay analysis, which reveals a time delay on the order of seconds between different locations (Martinez‐Calderon et al., 2016; Němec et al., 2014).…”
Section: Introductionmentioning
confidence: 94%
“…Many previous studies reported coherently modulated QP emissions that were simultaneously observed at conjugate points along the magnetic field line (Carson et al., 1965; Martinez‐Calderon et al., 2016, 2020; Titova et al., 2015). QP emissions can also be coherent across magnetic field lines, and multipoint observations from the ground (Carson et al., 1965) and equatorial satellites (Bezděková et al., 2020; Li et al., 2017; Němec et al., 2016) recorded coherent QP emissions across several hours in local time and several L‐shells. QP emissions had been used to study the propagation of whistler‐mode waves by tracing the waves with quasiperiodic rising‐tone structures (e.g., Němec et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of direct VLF measurements in the space with satellite instruments, the continuous ground-based observations can provide the unique possibility to study the temporal dynamics of the waves. In particular, still now many findings of properties and dynamics of different types of natural VLF emissions such as chorus, hiss, long series of QP emissions, have been found basing on the ground-based observations at Kannuslehto station (KAN) in Northern Finland (e.g., Bezděková et al, 2020;Demekhov et al, 2020;Kleimenova et al, 2015Kleimenova et al, , 2019Manninen et al, , 2014Manninen et al, , 2015Manninen et al, , 2016Manninen et al, , 2017Manninen et al, , 2020Manninen et al, , 2012Martinez-Calderon et al, 2019;Shklyar et al, 2020;Titova et al, 2017Titova et al, , 2015.…”
mentioning
confidence: 99%